Peran Penting Sarana dan Prasarana Dalam Pembelajaran Bimbingan Konseling di Sekolah - Sugiarto, Sambas; S, Neviyarni; Firman, Firman (Yayasan Darussalam Bengkulu, 2021)
Guidance and counseling facilities, infrastructure are a tool to support guidance and counseling activities. This study aims to create a comfortable and stable situation when the guidance and counseling service activities are underway. This study uses a qualitative approach with the category of library research (Library Research). The success of guidance and counseling services in schools is supported by the effective and efficient use of all existing guidance and counseling facilities and infrastructure in schools. The profile of existing facilities and infrastructure in these schools needs to be utilized and managed for the benefit of the guidance and counseling service process in schools, the process of guidance and counseling activities will run effectively and efficiently if supported by adequate facilities and infrastructure.